Transformation of Religious Moderation through Optimization of Rohis Activities: A Systematic Analysis of Islamic Values - Ijah Bahijah; Hamidah Hamidah; M. Fachjri Kurniawan; Khalimah Tussakdiyah; Anisa Musyarrof (KURAS Institute, 2025)
This study aims to examine the transformation of Islamic Spiritual Activities (Rohis) in shaping religious moderation in the school environment. The approach used is Systematic Literature Review (SLR), by capturing data from various national scientific articles through databases such as Google Scholar and Garuda. Data collection was carried out using keywords related to